Passive Voice and the Language of Translation: A Comparable Corpus-Based Study of Modern Greek Popular Science Articles - Malamatidou, Sofia (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2013)
Little research has been conducted so far into the translation-specific features that are dependent on both the source and the target language. This study aims at examining whether Modern Greek translated popular science articles differ from non-translated ones by being closer to the source language, which is English, in terms of the frequency and the word order of the passive voice constructions. This is one of the few Modern Greek studies that use a comparable corpus in order to better understand the nature of the translation practice. The corpus analysed consists of Modern Greek popular science articles and is divided into two subcorpora: the translated language corpus and the non-translated language corpus. The study indicates that there is substantial evidence that Modern Greek articles employ some translation-specific features which are dependent on the source language, at least in terms of some passive voice features. More importantly, it suggests that the non-translated texts tend to be similar to the translated ones, which are in turn closer to the English source texts. Even though it is early to conclude that translation encourages the different usage of particular linguistic features in non-translated texts, the data provide indirect evidence that translation is a potential field of language contact with important consequences.